Effect of Awareness and Perceived Self-Efficacy on Breast Cancer Preventive Behaviors in Women; A Case Study of Neyshabur City - Zakieh Sadat Hoseini; Hamid Tavakoli ghouchani; Hamidreza Mohaddes Hakak; Hossein Lashkardoost; Mehdi Khankolabi; Ali Mehri; Elahe Salari (Hamadan University of Medical Sciences, 2019)
Aims: Breast cancer is currently one of the main causes of women's death in the world. Having a healthy lifestyle and performing screening tests has an effective role in reducing the mortality due to this disease. The aim of the present study was to determine the effect of awareness and perceived self-efficacy of women of Neyshabur city on the preventive behaviors of breast cancer. Instruments & Methods: This cross-sectional descriptive-correlational study was carried out on 248 women aged 30-69 years old who referred to Neyshabur Health Services Centers. The subjects were selected by cluster sampling method. Data were collected by a researcher-made questionnaire after assessment of its validity and reliability by a self-report method. Data were analyzed by SPSS 19 software, using Pearson correlation coefficient and linear regression method. Findings: There was a significant positive correlation between the mean scores of awareness (r=0.179; p=0.005) and perceived self-efficacy of women (r=0.211; p=0.001) with the preventive behaviors of breast cancer. Totally, self-efficacy and awareness variables significantly predicted %67 of the breast cancer preventive behaviors (p<0.05). Conclusion: Increasing of women's perceived self-efficacy and awareness can be effective on promoting the prevention behaviors of breast cancer.